2012
DOI: 10.1063/1.4720426
|View full text |Cite
|
Sign up to set email alerts
|

Electrical breakdown of carbon nanotube devices and the predictability of breakdown position

Abstract: We have investigated electrical transport properties of long (>10 μm) multiwalled carbon nanotubes (NTs) by dividing individuals into several segments of identical length. Each segment has different resistance because of the random distribution of defect density in an NT and is corroborated by Raman studies. Higher is the resistance, lower is the current required to break the segments indicating that breakdown occurs at the highly resistive segment/site and not necessarily at the middle. This is consistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
2
1
0
Order By: Relevance
“…The generation of defects on the CNTs deteriorates the field emission properties. 32,33 The results support the notion that when densifying the film with a high concentration of nitric acid, the deterioration effect of the CNT film becomes dominant over the densification effect during field emission. We also evaluate field emission characteristics of the emitter using the Seppen−Katamuki (S−K) chart, as depicted in Figure 8c.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…The generation of defects on the CNTs deteriorates the field emission properties. 32,33 The results support the notion that when densifying the film with a high concentration of nitric acid, the deterioration effect of the CNT film becomes dominant over the densification effect during field emission. We also evaluate field emission characteristics of the emitter using the Seppen−Katamuki (S−K) chart, as depicted in Figure 8c.…”
Section: Resultssupporting
confidence: 74%
“…While the film is being densified, the defect density increases on the CNT surface, which becomes substantial at a high concentration of nitric acid exceeding 4 M, as illustrated in Figure . The generation of defects on the CNTs deteriorates the field emission properties. , The results support the notion that when densifying the film with a high concentration of nitric acid, the deterioration effect of the CNT film becomes dominant over the densification effect during field emission.…”
Section: Resultssupporting
confidence: 71%
“… 64 As J – V measurements have been performed in a vacuum atmosphere, the heat dissipation happens mostly through the NT and the electrodes. Also, it has been observed that the extremely resistive part of the NT is broken at a lower current which indicates that breakdown does not always occur at the middle part, 65 and also for shorter NTs, this happens away from the central part of the NT 66 due to the anisotropic temperature profile.…”
Section: Resultsmentioning
confidence: 99%